Bio-based anti-coagulant agent from microorganisms for natural rubber latex preservation - Abu Hassan, Aziana (2015)
Natural rubber (NR) latex is whitish fluid derived from latex ducts which are in a layer outside the cambium of rubber trees (Hevea Brasiliensis). Latex is a stable dispersion of cis-1,4-polyisoprene rubber in an aqueous phase that contain non-rubber substances such as carbohydrates, proteins and amino acids and a range of enzymes. Non-rubber constitute in NR latex encourage the proliferation of bacteria that causes latex destabilization and coagulation due to their metabolism activities. Preserved NR latex is referred to latex that will not undergo coagulation process to form a solid natural rubber. Ammonia and others chemical-based preservative agent such as tetramethylthiuramdisulphite/ zinc oxide (TMTD/ZNO) have negative drawbacks to the environment and human health. The approach on searching for biological based format for NR latex preservation was due to the current focus on generating biologically processing system. Therefore, the objective of the present study is to search for biological based anti-coagulant agent for NR latex short-term preservation with antimicrobial and surfactant properties from microorganisms present in environment related with NR. A total of 28 isolates comprises 20 bacterial isolates and eight fungal isolates were successfully obtained from field NR latex, coagulated NR latex and soil from rubber plantation area. Screening for antimicrobial activity was performed using disc diffusion method. The surfactant activity was evaluated by measuring the surface tension of the extracts. The emulsification capability was determined by measuring the droplets size and distribution of oil in water emulsions. The field NR latex stability was characterized by means of bacterial population, volatile fatty acid numbers (VFA), and NR latex viscosity. Out of 28 isolates, only four isolates exhibited antimicrobial activity namely, Aspergillus fumigatus S14, A. flavus S16, Phaeomoniella chlamydospora EM19 and Bacillus amyloliquefaciens S10b. Meanwhile, in surfactant activity screening assay, only five isolates out of 28 isolates exhibited surfactant activity in which comprises of one fungi Lambdasporium sp. FS31 and four bacteria (Enterococcus feacalis F11, Myroides odoratus F5, Bacillus pumilus S1b and EM23). Microbial extracts from B. amyloliquefaciens S10b performed better than the other isolates that exhibited antimicrobial activity in acting as antimicrobial agent in field NR latex. Surfactant activities from Lambdasporium sp. FS31 showed greater potential to enhance the colloidal stability of the rubber particles. Out of the nine isolates, four isolates namely, P. chlamydospora EM19, B. amyloliquefaciens S10b, Lambdasporium sp. FS31 and M. odoratus F5 were prepared in a mixture. Field NR latex in the presence of microbial extracts from B. amyloliquefaciens S10b with Lambdasporium sp. FS31 showed less bacterial activity and slow increment of VFA number resulting in minimal changes of the NR latex viscosity indicated a good NR latex stability. In conclusion, this study showed that these microorganisms have potential to be used as an anti-coagulant agent for NR latex preservation.